A Cross Sectional Study About the Prevalance of Potential Drug-drug Interactions in Various Inpatient Departments of a South Indian Government Headquarters Hospital using Prescription Analysis - Arumugavignesh, Murugakadavul; Prammanathan, Thenmozhi; Abishek, Rajaram; Vigneswaran, Rajagopal (Journal of Pharmacy Practice and Community Medicine)
Objectives: This study is focused on to identify the prevalence of potential drug-drug interactions among various inpatients’ departments of a government headquarters hospital in Tamil Nadu, India. Segregation of potential DDIs which were found in patients’ prescriptions according to their severity and examining the distribution of those DDIs in relevance to demographic features like gender and age are other objectives of this study. Materials and Methods: A prospective observational cross-sectional study was conducted with the periodicity of six months (between September 2021 and February 2022) in a government headquarters hospital of the state Tamil Nadu. This research includes six hundred and fifty- four (654) inpatients, including both male and female patients from various departments like general medicine, surgery, pediatric, psychiatric, post operative wards. Patients with serious illness and those who are not willing to participate were excluded from this study. Results: The average number of drug interaction per patient prescription was said to be 1.09. Number of prescriptions with 1 drug-drug interaction are 219. Fourteen prescriptions were found with more than six drug-drug interactions. Out of 718 potential DDIs, only 2 were contraindicated. The number of major DDIs was 335. Moderate drug interactions outnumbered minor drug interactions in our study. This study identified 2 contraindicated DDIs which were attributed to the same drug pair (ceftriaxone and ringer’s lactate solution) in two different pediatric prescriptions. Conclusion: Polypharmacy and drug-drug interactions are the widely recognized drug related problems. By mitigating polypharmacy issue, drug-drug interactions in prescriptions can be attenuated.
Keywords: Drug-drug interactions; Severity; Inpatients; Polypharmacy; Micromedex; Prescriptions